Algebraic theory of measure algebras - Bezushchak, O.O.; Oliynyk, B.V. (Доповіді НАН України, 2023)
A. Horn and A. Tarski initiated the abstract theory of measure algebras. Independently V. Sushchansky, B. Oliynyk and P. Cameron studied the direct limits of Hamming spaces. In the current paper, we introduce new examples of locally standard measure algebras and complete the classification of countable locally standard measure algebras. Countable unital locally standard measure algebras are in one-to-one correspondence with Steinitz numbers. Given a Steinitz number s such measure algebra is isomorphic to the Boolean algebra of s-periodic sequences of 0 and 1. Nonunital locally standard measure algebras are parametrized by pairs (s, r), where s is a Steinitz number and r is a real number greater or equal to 1. We also show that an arbitrary (not necessarily locally standard) measure algebra is embeddable in a metric ultraproduct of standard Hamming spaces. In other words, an arbitrary measure algebra is sofic. Абстрактна теорія алгебр з мірою була започаткована А. Хорном і А. Тарським. Незалежно від них В. Сущанський, Б. Олійник і П. Камерон досліджували прямі границі просторів Хемінга. У цій статті наведено нові приклади локально стандартних алгебр з мірою та завершено класифікацію зліченних локально стандартних алгебр з мірою. Зліченні унітальні локально стандартні алгебри з мірою знаходяться у взаємно однозначній відповідності з числами Стейніца. Для даного числа Стейніца s така алгебра з мірою ізоморфна булевій алгебрі s-періодичних послідовностей iз 0 та 1. Неунітальні локально стандартні алгебри з мірою параметризуються парами (s, r), де s — число Стейніца, а r — дійсне число, яке більше або дорівнює 1. Також показано, що довільна (не обов’язково локально стандартна) алгебра з мірою занурюється в метричний ультрадобуток стандартних алгебр з мірою. Іншими словами, довільна алгебра з мірою є софічною.